2022
DOI: 10.12984/egeefd.1072354
|View full text |Cite
|
Sign up to set email alerts
|

Kültüre Duyarlı Okul Psikolojik Danışmanlığında Bir Teknik: Kültürel Konulara Ön Ayak Olmak

Abstract: Counseling discipline has focused on multiculturalism for the last 40 years. As a result of this process, the multicultural counseling process has been conceptualized, and many theories and models have been developed in this regard. The most widely used multiculturalism models in Turkey as well as in the world consist of the knowledge, awareness and skill components. However, it has been observed that although many counselors working in the field are relatively competent in cultural knowledge and awareness lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In alignment with prior research findings (Erdur-Baker, 2007;Kağnıcı, 2013;Karaırmak, 2008;Meydan & Kağnıcı, 2018), our study revealed that participants from Türkiye tend to exclude discussions of multicultural aspects in their supervision sessions. Despite the alignment of Turkish literature with the international discourse on multicultural aspects within counselling and supervision (Akalın & Türküm, 2021;Aydoğan, 2022), our study's findings may be contextualized by the prevailing political climate in contemporary Türkiye. It is plausible that supervisors in Türkiye exhibit reluctance in addressing cultural dimensions of supervision and counselling, such as race, ethnicity, sexual orientation, religion, and socioeconomic background, due to concerns regarding potential reactions from students and institutions.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In alignment with prior research findings (Erdur-Baker, 2007;Kağnıcı, 2013;Karaırmak, 2008;Meydan & Kağnıcı, 2018), our study revealed that participants from Türkiye tend to exclude discussions of multicultural aspects in their supervision sessions. Despite the alignment of Turkish literature with the international discourse on multicultural aspects within counselling and supervision (Akalın & Türküm, 2021;Aydoğan, 2022), our study's findings may be contextualized by the prevailing political climate in contemporary Türkiye. It is plausible that supervisors in Türkiye exhibit reluctance in addressing cultural dimensions of supervision and counselling, such as race, ethnicity, sexual orientation, religion, and socioeconomic background, due to concerns regarding potential reactions from students and institutions.…”
Section: Discussionmentioning
confidence: 76%
“…Multicultural supervision has been consistently associated with favourable outcomes, including enhancements in supervisory alliance, supervisor satisfaction, counsellor skill development, counsellor self-efficacy, and overall counsellor competence (Crockett & Hays, 2015;Gatmon et al, 2001;Ladany et al, 1997). Drawing from practices implemented by counsellor educators in the US, the adoption of multicultural techniques, such as broaching, could potentially assist Türkiye's supervisors in navigating sensitive cultural issues (Aydoğan, 2022;Aydoğan, et al, 2022;Jones et al, 2019). Broaching involves a continuous effort to sensitively incorporate clients' and supervisees' cultural backgrounds while considering the socio-political realities, aiming to create meaningful and effective counselling interventions (Day-Vines et al, 2007;Jones et al, 2019).…”
Section: Implications and Recommendations For School Counsellor Educa...mentioning
confidence: 99%
“…In the current study, Q methodology was utilized to investigate how teacher candidates transformed their perceptions as a result of a culturally responsive education course. Q methodology has been widely adopted in social sciences (Aydogan et al, 2022;Watts & Stenner, 2023). In the current study, participants were asked to rank a set of prepared statements (Q set) based on their thoughts and opinions, using a scale that ranges from negative to positive.…”
Section: Q Methodologymentioning
confidence: 99%
“…The current study also supported this pattern by the lacking statistical relationship between self-advocacy and MCC. Counsellor educators and supervisors should focus on teaching skill-based interventions in their multicultural counselling classes (Aydoğan et al, 2022). In such classes, skill building activities may include role-plays, immersion experiences, real life scenarios and/or culture-focussed interviews with real clients.…”
Section: Implications For School Counsellor Educators and Supervisorsmentioning
confidence: 99%